Clinical supervisors' experiences of midwifery students' reflective writing: a process for mutual professional growth. Issue 1 (2nd January 2021) - Ekelin, M.; Kvist, L.J.; Thies-Lagergren, L.; Persson, E.K
ABSTRACT: Structured reflective writing during clinical placement has been shown to be valuable for students' learning and for their personal and professional development. The aim of this study was to examine clinical supervisors' experiences of midwifery students' daily written reflections on their practice at birthing units. A qualitative study was performed, and data were analysed using content analysis. In total 17 midwives working as clinical supervisors in the South of Sweden were interviewed using both focus groups and individual interviews. One main category 'A process for mutual professional growth', three categories and seven subcategories emerged from the analyses. The supervisors' experience was that reflective writing facilitated individualized supervision and initiated a loop of reflection. The way students wrote their reflections affected the feedback and was an aid for the supervisor to be active and flexible. The process of using written reflections was considered as a tool for following the progress of the students and the process of learning but also developed the midwife in her supervisory as well as in her professional role. The supervisors called for more time allotted, better organizational support, and clearer instructions for how to write feedback.